Analisis Price To Earning Ratio Dan Price To Book Value Dalam Pengambilan Keputusan Investasi - Mislinawati Mislinawati; Dewi Maya Sari (Universitas Teuku Umar, 2023)
This research was conducted to calculate and analyze the Price to Earning Ratio (PER) and Price to Book Value at state-owned banking companies for the 2018-2020 period. The data used is secondary data. The results showed that market value ratio analysis using the PER method, state-owned banking companies's share price can be said to be expensive because the PER value is higher than 10, while the results of market value ratio analysis using the PBV This research was conducted to calculate and analyze the price to earnings ratio (PER) and price to book value at state-owned banking company for the 2018–2020 period. The data used is secondary data. The results showed that, using market value ratio analysis using the PER method, state-owned banking companies’s share price can be said to be expensive because the PER value is higher than 10, while the results of market value ratio analysis using the PBV method state-owned banking companies's share price can be said to be expensive because for everyone share of state-owned banking companies investors must pay more than the book value of the shares. Overvalued conditions occurred in 2018–2020, so it is not recommended to invest in that year.